Legal, Certainty and Protection of the Investiments: A Comparative Perspective (Common Law, Civil Law) - Ulhoa Coelho, Fabio (International Journal of Insolvency Law, 2017)
[extract] The purpose of this article is to discuss the issue of legal certainty. It reviews the legal certainty in the ambit of Brazilian Law, a civil law jurisdiction. The concept of legal certainty is delimited and its importance for economy and commercial relations is discussed. The most important aspect of legal certainty is “ideology”. The judicial legitimacy of the same-sex family union in Brazil is a highly notable case in which we can see that a norm is interpreted differently when the ideology changes. As “ideology matters”, if a country wants to provide more legal certainty, it has to develop actions aiming at changing the ideology. The conclusion suggests the thesis that ideology would be the most important aspect in the matter of legal certainty also in common law jurisdictions.